EFFECTIVITY TEST ANTIBACTERIAL SENGGANI LEAF (Melastoma candidum) ON BACTERY Streptococcus mutans - Yelin Gloria; Dini Delfina; Yulitas Bachtiar (Universitas Negeri Medan, 2019)
Senggani leaves are one of the highland plants in Indonesia with the latin name Melastoma candidum. The results of phyitochemical screening that have been carried out show that senggani leaves contain tannin and flavonoid hich have an antibacterial function by inhibiting bacterial action in cell formation and even growth. The survey metode used is descriptive (for explanation of plants) and experimental (for an explanation of antibacterial test). In the bacterial test using a concentration of leaf extract of 6,25%, 12,5%, 25%, 50%, 75% and 100%. An placebo as positive control (+) and DMSO as a negative control (-). Antibacterial to streptococcus mutans (gram-positive bacteria) which at concentration of 6,25% has an average 12 mm, 12,5% has an average 13,56 mm, 25% has an average 15,30 mm, 50% on average 17,20 mm, 75% on average 18,10 mm and 100% have an average of 19,06 mm. So, senggani leaves have effect antibacterial to Streptoccous mutans.